THE DEVELOPMENT OF LINGUOCULTUROLOGY IN TEACHING THE HISTORY OF ENGLISH LANGUAGE (American Journal of Interdisciplinary Research and Development, 2023)
The article deals with the concept of «linguocultural competence» in teaching English. Its place in language system is defined. In modern studies on methods of teaching English language increasing attention is focused on the relation between language, history and culture. The acknowledgement of the importance of the cultural component in article is closely connected with the usage of cognitive approach.